The Effects of Interest Rates on Islamic and Conventional Banks: A Comparative Study of Monetary Policy Transmission Channels - Drissi, Salma; Guerguer, Wafa (European Journal of Islamic Finance, 2023)
This academic article focuses on analysing the transmission mechanism of monetary policy in a dual banking system composed of Islamic and conventional banks. The main objective is to identify the factors that influence the behavior of banks in response to monetary stimuli and to examine the hypothesis of an asymmetric transmission of monetary policy. To achieve this goal, a methodology based on the Vector Autoregression (VAR) model was used to analyze the relationship between interest rates and macroeconomic variables. The results of this study showed that the transmission of monetary policy is confirmed in a dual banking system through the channel of bank loans and that Islamic banks are more sensitive to changes in interest rates than conventional banks. These findings have important theoretical and methodological implications for understanding the mechanism of monetary policy transmission in a dual banking system and for monetary policy in general.